Effect of season on reproductive performance of ostrich (Struthio camelus) - C. Pandian; S.T. Selvan; R.Venkataramanan; H. Gopi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Effect of season on reproductive performance of ostrich was carried out at Post Graduate Research Institute in Animal Sciences, Tamil Nadu Veterinary and Animal Sciences University, Kattupakkam, Kanchipuram district in Tamil Nadu during 2014 - 2015. A total of 860 eggs were utilized for this study. The influence of season on reproductive performances viz., fertility, hatchability and embryonic mortality were studied. Season had a highly significant (P≤0.01) influence on fertility performance in ostrich, and higher per cent fertility were observed during northeast monsoon (34.18 ± 4.80) and winter (30.76 ± 5.51) than summer (12.78 ± 1.86) and southwest monsoon (10.13 ± 1.43) seasons. Similarly, higher total hatchability percentage was observed during northeast monsoon (12.29 ± 2.14) and winter (8.48 ± 1.44) followed by summer (4.85 ± 1.02) and southeast monsoon (3.69 ± 0.69) seasons. However, no significant difference was observed for fertile hatchability and embryonic mortality among different seasons. Study concluded that the reproductive performances in ostrich are seasonal dependent in tropical climate.